2022
DOI: 10.46300/91011.2022.16.10
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Procedure of Totally Tubeless PNL

Abstract: Mini percutaneous nephrolithotomy (mPNL) is a standard treatment for kidney stones larger than 1.5 cm, with the placement of a nephrostomy drainage at the end of it, which is considered the standard procedure, but tubeless/ totally tubeless mPNL techniques reduce postoperative discomfort in patients and shorten hospital stays. The aim of article was to compare the efficacy and safety of our proposed modified method of totally tubeless mPNL with control of the parenchymal canal, with existing methods of tubeles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The anatomical and functional results of this research are consistent with recent literature (12,17). In addition, studies have shown that the use of lightweight mesh is safer and with fewer complications than the PROLIFT system and medium-weight and heavyweight propylene mesh (18,(19)(20)(21). As for the anatomical results of this study concerning the Ba point following the POP-Q, they can be considered unsatisfactory in the medium and long term.…”
Section: Discussionsupporting
confidence: 88%
“…The anatomical and functional results of this research are consistent with recent literature (12,17). In addition, studies have shown that the use of lightweight mesh is safer and with fewer complications than the PROLIFT system and medium-weight and heavyweight propylene mesh (18,(19)(20)(21). As for the anatomical results of this study concerning the Ba point following the POP-Q, they can be considered unsatisfactory in the medium and long term.…”
Section: Discussionsupporting
confidence: 88%
“…It is also believed that the increase in bioactivity can be a consequence of the physical and chemical modification of the replaced material, namely: changes in the chemical composition of the surface layer, morphology and microstructure. [34][35][36][37][38] The high activity of Si-CPC is associated with the formation of silanol -SiOH groups on the surface of the material, which together with ions of calcium and phosphate, create a synergistic effect concerning the impact on reparative processes in the bone tissue. 35,39-41 Studies have shown that hydroxylapatite modified with silicate-ions (Si-HAP) has an augmented surface electronegativity that contains hydrophilic Si-OH groups that easily interact with polar groups of organic compounds, facilitating cell attachment and promoting the formation of a larger number of the implant-bone connections.…”
Section: Discussionmentioning
confidence: 99%
“…A microsurgical technique with subdural and subarachnoid "dry" space is a condition for the prevention of vascular and neural damage. Postoperative development of liquorrhea is the most common complication in these patients, often associated with inadequate sealing of the dura mater (38). Careful closure of the dura mater is important to prevent postoperative liquorrhea.…”
Section: Marković Et Al Described a Case Of Atypicalmentioning
confidence: 99%